Confining modeling of quark propagator - A. E. Radzhabov; X. L. Shang (European Physical Journal C: Particles and Fields)
Abstract A confining extension of the quark model with nonlocal currents is proposed. The quark propagator is modified by introducing a cut in $$α $$ α -space, which in momentum space corresponds to the subtraction of pole singularities. A two-phase structure is proposed for modeling the confinement-deconfinement phase transition. In the confined phase, the quark propagator does not have any pole singularities, while in the deconfined phase, there is a single quark pole.